2021
DOI: 10.1515/med-2021-0285
|View full text |Cite
|
Sign up to set email alerts
|

Sublingual immunotherapy increases Treg/Th17 ratio in allergic rhinitis

Abstract: Background Few studies investigated the effects of sublingual immunotherapy (SLIT) on the peripheral regulatory T cells (Tregs)/Th17 ratio. Objective To investigate the effectiveness of SLIT in children with allergic rhinitis (AR) and the effects on the Tregs/Th17 ratio. Methods This was a retrospective study of children who were treated for AR between April … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 38 publications
0
5
0
Order By: Relevance
“…Interestingly, some previous reported immunal changes after 1 year of AIT. 21 , 22 , 23 , 24 , 25 However, the different allergen type (mite vs cedar pollinosis), treatment method (SCIT vs SLIT), and treatment population (adult vs children) may explain the different results. Our data also showed that the percentages of Treg, Breg, and Tfr in the 3 years group increased significantly.…”
Section: Discussionmentioning
confidence: 99%
“…Interestingly, some previous reported immunal changes after 1 year of AIT. 21 , 22 , 23 , 24 , 25 However, the different allergen type (mite vs cedar pollinosis), treatment method (SCIT vs SLIT), and treatment population (adult vs children) may explain the different results. Our data also showed that the percentages of Treg, Breg, and Tfr in the 3 years group increased significantly.…”
Section: Discussionmentioning
confidence: 99%
“…SSs were evaluated in 23 studies ( 15 , 17 , 24 31 , 33 , 41 45 , 53 , 55 , 58 , 60 , 65 67 ), including 2332 patients in the SLIT group and 2380 in the non-SLIT group. Pooled analysis illustrated that compared with the non-SLIT group, the SLIT group had a significantly lower SS (pooled SMD: -0.99, 95%CI: -1.29, -0.69, I 2 = 95.1%, P < 0.001) ( Supplementary Figure 1 ).…”
Section: Resultsmentioning
confidence: 99%
“…Symptoms included itchy nose, sneezing, running nose, blocked nose, itchy eyes, etc. ( 17 , 24 , 25 ), and the Visual Analogue Scale (VAS) was also used for evaluation ( 15 , 26 ). Some studies recorded daily values ( 25 , 27 ), while some recorded scoring results over a period of time ( 28 , 29 ).…”
Section: Methodsmentioning
confidence: 99%
“…Recently, researchers have suggested that an imbalance between Th17 and Treg cells may also contribute to the pathogenesis of allergic disorders including AR [77]. Th17 cells can promote eosinophilic inflammation in AR whereas Treg cells may inhibit activation of Th2 cells, attenuating the response against the allergen [72,78].…”
Section: Allergic Rhinitismentioning
confidence: 99%